Effect of groove patterns on composite bond strength in bamboo-reinforced concrete - M. Sadique Ameen; Debarati Datta (Građevinar)
The use of bamboo as a reinforcement material in concrete has garnered attention in recent years due to its low cost, renewability, and high strength-to-weight ratio. However, the bond strength between bamboo and concrete is a crucial factor affecting the overall performance of bamboo-reinforced concrete structures. In this study, the bond between bamboo and concrete is investigated through pull-out tests. Three different groove patterns - rectangular, semi-circular, and V-notch - are examined for their bond strength. Various chemical treatments are also being explored to reduce the water absorption capacity of bamboo splints. The highest bond strengths achieved after using Bond Tite adhesive and bituminous paint are 1.94 MPa and 1.41 MPa, respectively. The findings of this study can be valuable in optimizing the design and construction of bamboo-reinforced concrete structures.